Socioeconomic and demographic factors associated with low birth weight in Nepal: Data from 2016 Nepal demographic and health survey - Benojir Ahammed; Md Maniruzzaman; Farzana Ferdausi; Md Menhazul Abedin; Md Tanvir Hossain (Wolters Kluwer Medknow Publications, 2020)
Introduction: Low birth weight (LBW) is an essential component for child mortality, and it also has dangerous effects on the mother's health. This study attempted to estimate the prevalence of the LBW among Nepalese children as well as to identify its socioeconomic and demographic determinants. Methods: For this study, 2016 Nepal Demographic and Health Survey data was used; 2,618 women having child were considered as respondents under precise specifications. The LBW of children was defined as birth weight <2500g. Descriptive statistics and multivariate logistic regression model were used to determine the risk factors of LBW based on the adjusted odds ratio (AOR) along with 95% confidence interval (CI) and P value (P < 0.05). Results: The overall prevalence of LBW in Nepal was 12.9% (95% CI: 11.6%-14.6%). The results of the multivariate analysis show that twin children (AOR: 22.538; 95% CI: 8.706-58.343) and female children (AOR: 1.444; 95% CI: 1.132-1.841) had a higher risk of LBW. Maternal age was also an important factor affecting LBW as findings suggest that the LBW tend to decrease with an increase of mother's age. Findings also indicate that children of the educated father with higher wealth status, maternal intake of iron tablets/syrup during pregnancy, and families having more than one child were safeguarding against LBW in Nepal. Conclusion: Risk factors of LBW are still problematic and unresolved in Nepal. Therefore, the implementation of social as well as health awareness programs, including maternal, neonatal and child health, are expected to introduce to curb LBW.